PENGEMBANGAN E-MODUL MENGGUNAKAN CANVA MATERI ORGAN PENCERNAAN MANUSIA DAN FUNGSINYA - Annisa Permata Sari; Lina Novita; Nur Hikmah (STKIP Subang, 2024)
Development of E-Modules Using Canva Material for the Human Digestive Organs and Their Functions. This research uses the type of R&D (research and development) research. The purpose of this research is for e-module developers using Canva material for the human digestive organs and their functions. The subjects of this study were fifth grade students at SDN Margajaya 3 Bogor City with a total of 35 students using ADDIE (Analaysis, Design, Development, Implementation, Evaluation). The progress of information and communication technology in the world of education is developing very well. Then do a limited trial to the respondents who have been determined. The validation results from media experts with a percentage of 91.25%, linguists with a percentage of 94.28%, material experts 1 with a percentage of 92%, and material experts 2 with a percentage of 100%. So thus the development of e-modules uses Canva material for the human digestive organs and their functions are